Engagement and access : innovative approaches for museums - Decker, Juilee (Innovative approaches for museums., 2015)
This book addresses how museums forge two-way communication and engaged participation through the use of community curation, social media, collaboration, and inquiry-based learning. Such approaches demonstrate how museums serve as thriving, central gathering places in communities and offer meaningful, creative educational experiences.